(3JNGejS GdHQOIs - (3TgGH GdOjf CMeO Hf SGde GdCPQYis; (3GdHhUjQj,J (B696 (3g` s
(3ChdgG (B:s
(3Ydi GdJQJjH (B: 1- (3eMeO GdQVG Hf CMeO GdfMhi (B: (3eGdi BQGc Mdja GdhLO hGdCde ChOi HLSec eG ChOi ef GdSbe s
(3BNQgG (B:s
(3hCPf dSMH UdGI efc OGFeI Ydi GdfHi Hefgd hefSLe eG QfMJ YPHGJ GdHGf eQjM UHG hCWQH GdYjS MGOi GdYjS HGdfZe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQgG eY eLehYI JNGejS hJSGHjYs
(3cJH GdJNejSGf GdChdGf Ydi GdgGeT hcJHJ GdJNGejS GdNeSI GdHGbjI Ydi gjFI (B7 8 (3ai UdH GdcJGHs
(3cJHJ CHjGJ GdHQOI cd HjJ HYO GdJNGejS cdgG HNW GdKdK s
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs